The determinants of knowledge-based economy development- the fundamental assumptions - Olszak, M. Celina; Ziemba, Ewa (Determinanty rozwoju gospodarki opartej na wiedzy – podstawowe założenia, 2011)
The goal of this paper is to identify the most important determinants of the KBE development. A special attention was paid to: education and human competences, innovations, economic and institutional policies, and ICT (Information Communication Technology),as they have been regarded as a foundation for the knowledge-based economy. This paper is addressed to representatives of enterprises, administrations, universities, and other parties who intend to participate actively in the KBE development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 206, s. 130-138
Keywords: knowledge-based economy; ICT; education; human competences; innovations; gospodarka oparta na wiedzy; kompetencje ludzi; innowacje